DIVERSITY OF PLANT FAMILY FABACEAE IN POCUT MEURAH INTAN GREAT FOREST PARK AREA, ACEH BESAR - Eriawati; Amin, Nurdin; Putri, Amalia; Aisyah, Aisyah (SciencePlus, 2025)
Fabaceae family plants are found everywhere, this is in accordance with the general habitat of Fabaceae plants that can grow in lowland areas. The Fabaceae family is one of the third largest families included in the members of the Angiospermae which are easily found in the Pocut Meurah Intan Forest Park area, Aceh Besar. The purpose of this study was to identify and analyze the diversity of plant species from the Fabaceae family. The study was conducted on November 16, 2024 using a descriptive observation method, by dividing the Tahura area into several plots. Then, samples were taken to be identified based on the characteristics of the Fabaceae family. The results of this study found 6 species from the Fabaceae family, namely acacia (Acasia auriculiformis), mimosa pudica (Mimosa pudica), tamarind (Tamarindus indica), keranji (Dialium indum), telang (Clitoria ternatea), angsana (Pterocapus inducus). So it can be concluded that in the Pocut Meurah Intan Tahura area there are several species from the fabaceae family